(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
The aim of this work is to measure concentration of some atmosphere components (CO2, NH3, O3, CH4) by using TDLAS (Tunable Diode Laser Absorption Spectroscopy) under different pressure (1 atm,100 mbar,72.5 mbar,50mbar,10mbar). This work had done by using HITRAN (HIgh Resolution TRANsmission molecular absorption data base) database to define the density of spectral line and define the present gas by knowing the wavenumber where absorption was happened, then concentration of each gas in the sample has been calculated by using optic path length inside the multi reflections cell, deferent pressure and intensity of spectral line. This system was considered as LIDAR (Light Detection And Ringing) in- situe for gas detection and concentration measuring.